Carcinosarcoma of the Ureter with a Small Cell Component: Report of a Rare Pathologic Entity and Potential for Diagnostic Error on Biopsy - Kent Newsom; Bayo Tojuola; Samer Al-Quran; Sijo Parekattil; William Hamilton; Lizette Vila Duckworth (Hindawi Limited, 2014)
Carcinosarcomas of the ureter are rare biphasic neoplasms, composed of both malignant epithelial (carcinomatous) and malignant mesenchymal (sarcomatous) components. Carcinosarcomas of the urinary tract are exceedingly rare. We report a unique case of a carcinosarcoma of the ureter with a chondrosarcoma and small cell tumor component arising in a 68-year-old male who presented with microscopic hematuria. CT intravenous pyelogram revealed right-sided hydroureter and hydronephrosis with thickening and narrowing of the right ureter. The patient underwent robot-assisted ureterectomy with bladder cuff excision and subsequent adjuvant chemotherapy. The patient is disease-free at 32 months after treatment. We provide a brief synoptic review of carcinosarcoma of the ureter and bladder with utilization of immunohistochemical (IHC) stains and potential diagnostic pitfalls.